Impact pathways from seeds to nutrition - Nabuuma, Deborah; Hoang The, Ky; Reimers, Christine; Raneri, Jessica Evelyn; Nguyen Thi Thuy, Lan; Gauchan, Devendra; Stomph, TjeerdJan; Swaans, Cornelis P.M. (Bioversity International and the International Center for Tropical Agriculture, 2020)
To elucidate how, and under what conditions, increased access and use of high-quality seed translates into nutrition security among smallholder farmers, four theoretical pathways from seeds to nutrition were envisioned: the nutrient-dense seed pathway, the seed diversity pathway, the seed value chain pathway, and the seed security and resilience pathway. Across the four pathways, several factors that influence the impact of seed system directed interventions on nutrition and food security were identified. The proposed theoretical pathways can be used to not only design seed system interventions that target nutrition and food security, but also build a solid evidence base for the pathways.